Kualitas Pelayanan Pada Klinik PKU Muhammadiyah Kitamura Pontianak - Devi Yasmin (Universitas Muhammadiyah Pontianak, 2014)
This study aimed to analyze the quality of PKU Muhammadiyah Kitamura Clinic services. quality dimensions measured are Tangible (Tangible), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Guarantee and Assurance), Empathy (Empathy). This type of research is descriptive. Data collection techniques using a questionnaire (questionnaire), interviews, observation and documentation study. The study population was patients who seek treatment at the clinic ever PKU Muhammadiyah Kitamura. A sample set of 100 people, which is gained through judgment sampling. The analysis tool is servqual analysis and Cartesian diagram. From the analysis servqual, it can be seen that the difference in the average level of expectations with the level of satisfacti on is 0.69 and the results of research Cartesian diagram, known to the average value of patient satisfaction at PKU Muhammadiyah Kitamura Clinic was 4.05 and the average value the benefit of patients is 4.74. These results indicate that patients feel dissatisfied with the quality of service at PKU Muhammadiyah Kitamura Clinic.